2013
DOI: 10.1007/s00410-013-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

TTG-type plutonic rocks formed in a modern arc batholith by hydrous fractionation in the lower arc crust

Abstract: We present the geochemistry and intrusion pressures of granitoids from the Kohistan batholith, which represents, together with the intruded volcanic and sedimentary units, the middle and upper arc crust of the Kohistan paleo-island arc. Based on Al-in-hornblende barometry, the batholith records intrusion pressures from *0.2 GPa in the north (where the volcano-sedimentary cover is intruded) to max. *0.9 GPa in the southeast. The Al-in-hornblende barometry demonstrates that the Kohistan batholith represents a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…It is now widely accepted that the early continental crust (mostly TTG series) was formed by melting of basaltic lithologies, leaving behind amphibolite, garnet‐amphibolite, or eclogite residues (Foley et al, ; Hastie et al, ; Johnson et al, ; Moyen, ; Nagel et al, ; Polat et al, ; Qian & Hermann, ; Rapp et al, ). It is also argued that Archean TTG gneisses can be formed by extensive fractional crystallization from a mafic precursor (Dessimoz et al, ; Jagoutz et al, ; Kamber et al, ; Kleinhanns et al, ). Such a process, however, has not seriously been considered in the past studies simply because the corresponding mafic‐ultramafic residue cumulates left during the fractional process are not evident in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now widely accepted that the early continental crust (mostly TTG series) was formed by melting of basaltic lithologies, leaving behind amphibolite, garnet‐amphibolite, or eclogite residues (Foley et al, ; Hastie et al, ; Johnson et al, ; Moyen, ; Nagel et al, ; Polat et al, ; Qian & Hermann, ; Rapp et al, ). It is also argued that Archean TTG gneisses can be formed by extensive fractional crystallization from a mafic precursor (Dessimoz et al, ; Jagoutz et al, ; Kamber et al, ; Kleinhanns et al, ). Such a process, however, has not seriously been considered in the past studies simply because the corresponding mafic‐ultramafic residue cumulates left during the fractional process are not evident in nature.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the experimental results of Müntener et al (), Kleinhanns et al () concluded that hydrous melts, which underwent extensive fractional crystallization of garnet/amphibole, pyroxenes, and minor plagioclase, could evolve to TTG‐like melts. Field observation and geochemical analyses of Jagoutz et al () indicate that some TTG‐like granitoids in the Kohistan arc can form by hydrous high‐pressure differentiation of primitive arc magmas in subduction zones. Similar conclusions were also reached from the exposed lower crust in the Chelan Complex.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is the standard model for granitic magmatism in the Andes (e.g., Hildreth and Moorbath, 1988;Kay and Mahlburg-Kay, 1991;Petford et al, 2000;Otamendi et al, 2009;Goss et al, 2011), as well as for ancient island arcs such as those exposed in crustal sections in Pakistan (Jagoutz, 2010;Jagoutz et al, 2011Jagoutz et al, , 2013. There is also growing support for the generation of Archean TTG in such a setting (e.g., Polat et al, 2002;Nagel et al, 2012;Polat, 2012).…”
Section: Generation Of Granitic Magmas In Subduction Zonesmentioning
confidence: 99%
“…Atherton and Petford (1993) identified such granitoids in the Andes some twenty years ago and Jagoutz et al (2013) recently did the same in the Kohistan island arc.…”
Section: Generation Of Granitic Magmas In Subduction Zonesmentioning
confidence: 99%
See 1 more Smart Citation